Far infrared ceramic muscle and bone patch and preparation method thereof

By etching and optimizing the matrix material of the far-infrared ceramic powder, the problem of low emission efficiency of far-infrared ceramic patches is solved, and the emissivity of far-infrared ceramics and the therapeutic effect of the muscle patches is significantly improved.

CN119139274APending Publication Date: 2024-12-17TONGHUA WANTONG PHARMACY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371050.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The matrix materials in existing far-infrared ceramic patches may hinder the conduction of far-infrared rays, resulting in the unsatisfactory emission efficiency of far-infrared ceramic microbeads and reducing the physical therapy effect.

Method used

The far-infrared ceramic powder is pretreated using etching solution, including etching with aqueous hydrochloric acid solution and silver nitrate, copper nitrate and other etching solution, and the matrix material is added to the matrix material to improve the emissivity and matrix of the ceramic. The permeability of the material.

Benefits of technology

It significantly improves the emissivity of far-infrared ceramics, reduces the influence of matrix materials on far-infrared radiation, and enhances the therapeutic effect of bone patches, especially when copper-silver ion etching liquid is added.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067591180000041
    Figure BDA0005067591180000041
  • Figure BDA0005067591180000051
    Figure BDA0005067591180000051
Patent Text Reader

Abstract

The invention relates to a far-infrared ceramic muscle and bone patch and a preparation method thereof, and belongs to the field of external medicines. The invention relates to a far-infrared health-care mask which comprises a matrix material, far-infrared ceramic powder and a flavoring agent, the far-infrared ceramic powder is pretreated by an etching solution, and the etching solution is a hydrochloric acid aqueous solution. The etching solution also comprises silver nitrate and copper nitrate; and further preferably, the etching liquid is 0.1 to 10 mol / L of silver nitrate, 0.1 to 10 mol / L of copper nitrate and 0.1 to 10 mol / L of a hydrochloric acid aqueous solution. The matrix material further comprises activated carbon and / or nano-zinc oxide. The invention further provides a preparation method and application of the far-infrared ceramic muscle and bone paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a far-infrared ceramic tendon and bone patch and a preparation method thereof, belonging to the field of external medicines. Background Art

[0002] Far-infrared rays (Far-Infrared Rays, FI R) are invisible light waves in the electromagnetic spectrum, with a wavelength range of 3 to 1000 microns. Studies have shown that far-infrared rays have a variety of biological effects on the human body, especially in the wavelength range of 8 to 14 microns, which have strong penetration into human tissues and can effectively promote blood circulation, increase cell metabolism and relieve muscle fatigue.

[0003] Far-infrared ceramic materials can continuously release energy in the far-infrared band after absorbing energy from the human body or the environment. Generally speaking, the mechanism of radiation emitted by ceramic materials is the radiation generated by two-phonons and multi-phonons of the non-resonant effect of polar vibration. High-radiation ceramic materials all have extremely strong infrared-activated polar vibrations, and these polar vibrations have extremely strong non-harmonic effects. Modern research shows that far-infrared rays have two biological effects-far-infrared thermal biological effects and non-thermal biological effects. Both of these biological effects have positive medical and health effects on the human body. Compared with other health materials, they have stronger radiation capabilities, good thermal effects and resonance effects. Their resonance effect causes biological molecules to produce a resonance absorption effect, which excites the molecular energy levels of organisms and is at a higher resonance energy level, but the mechanism of the resonance effect on the human body is still unclear.

[0004] Taking advantage of this characteristic, far-infrared ceramics are widely used in health care products, such as far-infrared physiotherapy devices, health clothing and medical patches. Far infrared rays can not only improve local blood circulation, but also speed up the recovery of the inflammatory site, reduce inflammatory reactions and relieve pain. The physiotherapy effect of far-infrared ceramics has been widely used in various health care products on the market. Existing far-infrared ceramic patches usually adopt the method of embedding far-infrared ceramic powder or microbeads into matrix materials, and achieve continuous far-infrared radiation effects by applying them to the surface of the human body. Since this type of patch does not contain small molecule drug ingredients, it has the advantages of safe use and no obvious side effects, and is suitable for long-term use. However, some matrix materials in existing far-infrared patches may hinder the conduction of far-infrared rays, resulting in unsatisfactory emission efficiency of far-infrared rays, reducing the physiotherapy effect of ceramic microbeads, so improving the radiation efficiency of far-infrared ceramics is a key issue in the current technical field. Summary of the invention

[0005] The first aspect of the present invention is to provide a far-infrared ceramic bone and muscle patch, which includes: a matrix material, far-infrared ceramic powder and a flavoring agent, wherein the far-infrared ceramic powder is pre-treated with an etching solution, and the etching solution is a hydrochloric acid aqueous solution.

[0006] In one embodiment, the etching solution is a 0.1-10 mol / L hydrochloric acid aqueous solution; more preferably a 0.5-2 mol / L hydrochloric acid aqueous solution; more preferably a 1 mol / L hydrochloric acid aqueous solution

[0007] In another embodiment, the etching solution further comprises silver nitrate and copper nitrate; further preferably, the etching solution is 0.1-10 mol / L silver nitrate, 0.1-10 mol / L copper nitrate and 0.1-10 mol / L hydrochloric acid aqueous solution; further preferably, the etching solution is 0.5 mol / L silver nitrate, 0.5 mol / L copper nitrate and 1 mol / L hydrochloric acid aqueous solution.

[0008] In another embodiment, the far-infrared ceramic bone and muscle patch comprises: 300-500 parts by weight of a matrix material, 20-50 parts by weight of a far-infrared ceramic powder, and a flavoring agent.

[0009] In another embodiment, the matrix material includes 5-25 parts by weight of mesh rubber, 50-100 parts by weight of rosin, 150-300 parts by weight of lithopone, 10-20 parts by weight of liquid paraffin, 10-20 parts by weight of white vaseline, 10-20 parts by weight of lanolin, 1-3 parts by weight of lemon yellow, 0.1-1 parts by weight of milk chocolate brown, 0.05-0.2 parts by weight of fruit green, and 0.5-2 parts by weight of sunset yellow. Further, the matrix material includes 15 parts by weight of mesh rubber, 75 parts by weight of rosin, 239.6 parts by weight of lithopone, 16.6 parts by weight of liquid paraffin, 19.5 parts by weight of white vaseline, 19.5 parts by weight of lanolin, 1.54 parts by weight of lemon yellow, 0.43 parts by weight of milk chocolate brown, 0.11 parts by weight of fruit green, and 0.82 parts by weight of sunset yellow.

[0010] In a further embodiment, the matrix material further comprises 3-5 parts by weight of activated carbon and / or 3-5 parts by weight of nano zinc oxide.

[0011] In yet another embodiment, the flavoring agent is a mint flavoring agent.

[0012] The second aspect of the present invention is to provide a method for preparing a far-infrared ceramic tendon and bone patch, which comprises:

[0013] (1) Pretreatment of far-infrared ceramic powder: etching the far-infrared ceramic powder with an etching solution at room temperature for 5 minutes, then taking out the ceramic powder and washing it with deionized water to obtain pretreated far-infrared ceramic powder;

[0014] (2) First, take the plasticized mesh rubber and place it in a kneading machine for kneading for 100-120 minutes, then add adhesives such as rosin, lead powder, liquid paraffin, white vaseline, lanolin, lemon yellow, milk chocolate brown, fruit green and sunset yellow, and then add activated carbon and / or nano zinc oxide, and knead for 30-40 minutes to obtain a medical pressure-sensitive adhesive; then add the far-infrared ceramic powder and mint flavoring agent obtained in step 1) to the medical pressure-sensitive adhesive; knead for 60-120 minutes, mix evenly, discharge the material, place it in a clean container and let it stand for 36 hours, then apply the glue paste to the stretch fabric through a coating machine, slice it with a slicer, and package it.

[0015] The third aspect of the present invention is to provide the use of the far-infrared ceramic bone and muscle patch in the preparation of a drug for treating pain. The pain is caused by scapulohumeral periarthritis, cervical spondylosis, lumbar disc herniation, rheumatoid arthritis, knee joint pain in the neck, shoulders, waist, legs, joints, and muscles.

[0016] The present invention finds that the far-infrared ceramic bone and muscle patch has a significantly lower far-infrared emissivity than the ceramic powder raw material, and the emissivity problem can be significantly overcome by etching the far-infrared ceramic, especially by using an etching solution with copper and silver ions added, which can not only significantly increase the emissivity of the far-infrared ceramic but also reduce the influence of the matrix material of the bone and muscle patch on the far-infrared radiation. In addition, this effect can be further improved by adjusting the matrix material. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0018] The far-infrared ceramic powder used in the following embodiments was purchased from Hebei Hengyue Mineral Products Co., Ltd.; its particle size is between 10-100 microns, and its oxide composition (by weight) is SiO2: 41%, Al2O3: 32%, B2O3: 11%, FeO: 9%, Fe2O3: 4%, Na2O: 3%; the emissivity in the far-infrared band is 0.896.

[0019] Example 1 Effect of far-infrared ceramic pretreatment on the far-infrared emissivity of the tendon and bone patch

[0020] (1) Emissivity of untreated far-infrared ceramic bone patch samples

[0021] Preparation of bone and muscle patch samples: first take 15.00kg of plasticized mesh rubber and place it in a kneading machine for 100-120 minutes, then add adhesive rosin 75.00kg, lead powder 239.60kg, liquid paraffin 16.60kg, white vaseline 19.50kg, lanolin 19.50kg, lemon yellow 1.54kg, milk chocolate brown 0.43kg, fruit green 0.11kg, sunset yellow 0.82kg and knead for 30-40 minutes to obtain medical pressure-sensitive adhesive. Then add 34.00kg of far-infrared ceramic powder and 5.90kg of mint flavoring agent to the medical pressure-sensitive adhesive and knead for 60-120 minutes, mix evenly, discharge, place in a clean container and let stand for 36 hours, take part of the adhesive paste, dry and crush into powder for standby use.

[0022] Far infrared emissivity test method: Use German BRUKER-80V Fourier transform infrared spectrometer to test the infrared emission and absorption performance of the sample. When testing the infrared absorption performance of the sample, mix the sample with potassium bromide at a mass ratio of 1:100, and test the sample at 713-1250cm in a vacuum state. -1 The infrared absorption performance of the band corresponds to the wavelength of 8-14μm. When testing the infrared emission performance of the sample, the black body is used as the standard sample.

[0023] The results show that the emissivity of the bone and muscle patch sample in the 8-14μm band is 0.835; compared with the reflectivity of the far-infrared ceramic powder sample alone (0.896), the far-infrared emissivity of the finished bone and muscle patch is significantly reduced. This may be related to the influence of the matrix material in the bone and muscle patch on the emissivity of the far-infrared ceramic.

[0024] (2) Pretreatment of far-infrared ceramics

[0025] In order to improve the far-infrared emission performance of the tendon and bone patch, the present invention adopts a pretreatment method to increase the emissivity of the far-infrared ceramic.

[0026] Treatment method 1: Use 1 mol / L hydrochloric acid aqueous solution to etch the far-infrared ceramic powder at room temperature for 5 minutes, then take out the ceramic powder and wash it with deionized water to obtain sample 1; sample 1 is further made into a tendon and bone patch sample (same method as above) to obtain sample 3.

[0027] Treatment method 2: Use 1 mol / L sodium hydroxide aqueous solution to etch the far-infrared ceramic powder at room temperature for 5 minutes, then take out the ceramic powder and wash it with deionized water to obtain sample 2; Sample 2 is further made into a tendon and bone patch sample (same method as above) to obtain sample 4.

[0028] The above samples were tested for far infrared emission performance (same method as above), and the specific results are as follows:

[0029] Emissivity Sample 1 0.913 Sample 2 0.906 Sample 3 0.872 Sample 4 0.841

[0030] The above results show that the emission performance of far-infrared ceramics can be improved by pre-treating them with etching methods. In particular, etching with hydrochloric acid can significantly improve the emission performance of far-infrared ceramics, while etching with sodium hydroxide has no significant improvement on the emission performance. However, after the tendon-bone patch samples were made, the emission performance also showed a significant decrease.

[0031] (3) Optimal hydrochloric acid etching conditions

[0032] First, the effect of hydrochloric acid concentration on the performance of far-infrared ceramics was explored. 0.5 mol / L, 2 mol / L and 4 mol / L hydrochloric acid were used to treat the ceramics according to the above method. Then the treated ceramic powder was directly taken to test the far-infrared emission performance. The specific results are as follows:

[0033]

[0034]

[0035] From the above results, it can be seen that in the treatment of ceramics, the far-infrared emission performance of the ceramics is best when treated with 1-2 mol / L hydrochloric acid.

[0036] Secondly, the effect of etching catalyst on the performance of far-infrared ceramics was explored. Silver nitrate and copper nitrate were added to the hydrochloric acid solution as etching catalysts, and then the far-infrared ceramics were etched. The specific groups are as follows:

[0037] Silver nitrate (mol / L) Copper nitrate (mol / L) Hydrochloric acid (mol / L) Group 1 0.5 - 1 Group 2 - 0.5 1 Group 3 0.5 0.5 1

[0038] Each group treated the far-infrared ceramic for 5 minutes, then took out the ceramic powder and washed it with deionized water to obtain samples 1-3 (corresponding to groups 1 to 3 respectively), and then took part of samples 1-3 to prepare tendon and bone patch samples, and obtained samples 4-6 respectively.

[0039] The specific results are as follows:

[0040] Emissivity Sample 1 0.924 Sample 2 0.918 Sample 3 0.935 Sample 4 0.879 Sample 5 0.896 Sample 6 0.921

[0041] From the above results, it can be seen that the far-infrared emissivity of samples 1 and 4, which only add silver ions, is further improved in terms of ceramic raw materials, but the improvement of the tendon and bone patch samples is not significant. The far-infrared emissivity of samples 2 and 5, which only add copper ions, is not significantly improved, but the emissivity of the tendon and bone patch samples can be significantly improved. For samples 3 and 6, which add silver ions and copper ions at the same time, the emissivity of ceramic raw materials and tendon and bone patches is very obvious. The principle may be related to the different changes in the surface structure of ceramic particles caused by etching with different metal ions. The specific principle exploration requires further research to achieve.

[0042] Example 2 Improvement of the matrix material of the tendon and bone patch

[0043] In order to further improve the performance of the far-infrared ceramic bone and muscle patch, the present invention also improves and optimizes the matrix material of the bone and muscle patch. On the basis of the original matrix material formula of Example 1 (see Part (1) of Example 1), the above four materials are selected from the aspects of far-infrared enhancement (nano zinc oxide), high permeability carrier (hyaluronic acid), anti-interference agent (activated carbon), and enhanced far-infrared permeability material (silicone gel) and are added to the original matrix material formula at a ratio of 1%. During the preparation process, the above four materials are added at the same time as rosin and other materials. Then, sample 6 in Part (3) of Example 1 is used as the far-infrared ceramic material to prepare four kinds of bone and muscle patches and measure the far-infrared emissivity. The specific results are as follows:

[0044] Emissivity Nano zinc oxide 0.927 Hyaluronic acid 0.911 Activated carbon 0.932 Silicone Gel 0.922

[0045] From the above results, it can be seen that under the condition of equal addition, nano zinc oxide and activated carbon significantly improve the far-infrared emission performance of the tendon patch, while hyaluronic acid and silicone gel have no obvious effect.

[0046] Example 3 Preparation of Far Infrared Ceramic Bone and Muscle Patch

[0047] (1) Pretreatment of far-infrared ceramic powder: The far-infrared ceramic powder was etched at room temperature using 0.5 mol / L silver nitrate, 0.5 mol / L copper nitrate and 1 mol / L hydrochloric acid aqueous solution for 5 minutes, and then the ceramic powder was taken out and washed with deionized water to obtain pretreated far-infrared ceramic powder;

[0048] (2) First, take 15.00 kg of the plasticized mesh rubber and place it in a kneading machine for kneading for 100-120 minutes, then add 75.00 kg of adhesive rosin, 239.60 kg of lead powder, 16.60 kg of liquid paraffin, 19.50 kg of white vaseline, 19.50 kg of lanolin, 1.54 kg of lemon yellow, 0.43 kg of milk chocolate brown, 0.11 kg of fruit green, 0.82 kg of sunset yellow and 3.88 kg of activated carbon, and knead for 30-40 minutes to obtain a medical pressure-sensitive adhesive. Then, add 34.00 kg of the far-infrared ceramic powder obtained in step 1) and 5.90 kg of mint flavoring agent to the medical pressure-sensitive adhesive; knead for 60-120 minutes, mix evenly, discharge the material, place it in a clean container and let it stand for 36 hours, then apply the glue paste to the elastic cloth through a coating machine, slice it with a slicer, and package it.

[0049] Example 4 Preparation of Far Infrared Ceramic Muscle and Bone Patch

[0050] (1) Pretreatment of far-infrared ceramic powder: The far-infrared ceramic powder was etched at room temperature using 0.5 mol / L silver nitrate, 0.5 mol / L copper nitrate and 1 mol / L hydrochloric acid aqueous solution for 5 minutes, and then the ceramic powder was taken out and washed with deionized water to obtain pretreated far-infrared ceramic powder;

[0051] (2) First, 15.00 kg of the plasticized mesh rubber is placed in a kneading machine for kneading for 100-120 minutes, and then 75.00 kg of adhesive rosin, 239.60 kg of lead powder, 16.60 kg of liquid paraffin, 19.50 kg of white vaseline, 19.50 kg of lanolin, 1.54 kg of lemon yellow, 0.43 kg of milk chocolate brown, 0.11 kg of fruit green, 0.82 kg of sunset yellow and 3.88 kg of nano zinc oxide are added, and kneaded for 30-40 minutes to obtain a medical pressure-sensitive adhesive. Then, 34.00 kg of the far-infrared ceramic powder obtained in step 1) and 5.90 kg of mint flavoring agent are added to the medical pressure-sensitive adhesive; kneaded for 60-120 minutes, mixed evenly, discharged, placed in a clean container and left to stand for 36 hours, and then coated on the elastic cloth by a coating machine, sliced ​​by a slicer, and packaged.

Claims

1. A far-infrared ceramic tendon and bone patch, comprising: The invention relates to a matrix material, a far-infrared ceramic powder and a flavoring agent. The far-infrared ceramic powder is pretreated with an etching solution, and the etching solution is a hydrochloric acid aqueous solution.

2. The far-infrared ceramic bone patch according to claim 1, characterized in that: The etching solution is a 0.1-10 mol / L hydrochloric acid aqueous solution.

3. The far-infrared ceramic bone patch according to claim 2, characterized in that: The etching solution is a 0.5-2 mol / L hydrochloric acid aqueous solution.

4. The far-infrared ceramic bone and muscle patch according to claim 1, characterized in that: The etching solution also contains silver nitrate and copper nitrate; the etching solution is 0.1-10 mol / L silver nitrate, 0.1-10 mol / L copper nitrate and 0.1-10 mol / L hydrochloric acid aqueous solution.

5. The far-infrared ceramic bone and muscle patch according to claim 4, characterized in that: The etching solution is 0.5 mol / L silver nitrate, 0.5 mol / L copper nitrate and 1 mol / L hydrochloric acid aqueous solution.

6. The far-infrared ceramic bone and muscle patch according to claim 1, characterized in that: The far-infrared ceramic bone and muscle patch comprises: 300-500 parts by weight of a matrix material, 20-50 parts by weight of a far-infrared ceramic powder and a flavoring agent.

7. The far-infrared ceramic bone and muscle patch according to claim 6, characterized in that: The matrix material comprises 5-25 parts by weight of mesh rubber, 50-100 parts by weight of rosin, 150-300 parts by weight of lithopone, 10-20 parts by weight of liquid paraffin, 10-20 parts by weight of white vaseline, 10-20 parts by weight of lanolin, 1-3 parts by weight of lemon yellow, 0.1-1 parts by weight of milk chocolate brown, 0.05-0.2 parts by weight of fruit green and 0.5-2 parts by weight of sunset yellow.

8. The far-infrared ceramic muscle and bone patch according to claim 7, characterized in that: The matrix material also includes 3-5 parts by weight of activated carbon and / or 3-5 parts by weight of nano zinc oxide.

9. A method for preparing the far-infrared ceramic bone and muscle patch according to any one of claims 1 to 8, comprising: (1) Pretreatment of far-infrared ceramic powder: etching the far-infrared ceramic powder with an etching solution at room temperature for 5 minutes, then taking out the ceramic powder and washing it with deionized water to obtain pretreated far-infrared ceramic powder; (2) First, take the plasticized mesh rubber and place it in a kneading machine for kneading for 100-120 minutes, then add adhesives such as rosin, lead powder, liquid paraffin, white vaseline, lanolin, lemon yellow, milk chocolate brown, fruit green and sunset yellow, and then add activated carbon and / or nano zinc oxide, and knead for 30-40 minutes to obtain a medical pressure-sensitive adhesive; then add the far-infrared ceramic powder and mint flavoring agent obtained in step 1) to the medical pressure-sensitive adhesive; knead for 60-120 minutes, mix evenly, discharge the material, place it in a clean container and let it stand for 36 hours, then apply the glue paste to the stretch fabric through a coating machine, slice it with a slicer, and package it.

10. Use of the far-infrared ceramic bone and muscle patch as claimed in any one of claims 1 to 8 in the preparation of a drug for treating pain; the pain is pain in the neck, shoulders, waist, legs, joints and muscles caused by scapulohumeral periarthritis, cervical spondylosis, lumbar disc herniation, rheumatoid arthritis and knee joints.